2009
DOI: 10.4293/108680809x1258998404604
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cholecystectomy in Elderly Patients

Abstract: Laparoscopic surgery can be safely applied in the elderly. Complications can be minimized by carefully selecting patients aged 80 years or older and operating on these patients with experienced teams with good technical capabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
52
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 22 publications
8
52
1
3
Order By: Relevance
“…This was comparable with other studies, like 2% as observed by Bhasin et al, 3.2% by Mulhim et al, and 0% by Duca et al [20,21,28] We found contracted or shrunken gall bladder in 4% cases, as compared to 15.07% found by Lal et al [29] Conversion to Open Cholecystectomy was required in 8%. This was comparable to the conversion rate of 12% as observed by Shah et al, 4% by Bhasin et al, and 8% by Yetkin et al [19,20,27] …”
Section: Disscusionsupporting
confidence: 89%
See 1 more Smart Citation
“…This was comparable with other studies, like 2% as observed by Bhasin et al, 3.2% by Mulhim et al, and 0% by Duca et al [20,21,28] We found contracted or shrunken gall bladder in 4% cases, as compared to 15.07% found by Lal et al [29] Conversion to Open Cholecystectomy was required in 8%. This was comparable to the conversion rate of 12% as observed by Shah et al, 4% by Bhasin et al, and 8% by Yetkin et al [19,20,27] …”
Section: Disscusionsupporting
confidence: 89%
“…[19,21,27] Difficult Calot's triangle was observed in 22 cases. In comparison, difficult Calot's triangle was found by Shah et al in 12% cases, Yetkin et al in 5.3%, and Duca et al in 9.8%.19, [27,28] In our study, calculus impacted at the neck of gall bladder or Hartmann's pouch was found in 10%. This was similar to the findings observed by Lal et al (11 out of 73 cases; 15.07%).…”
Section: Disscusionmentioning
confidence: 99%
“…Studies suggested that LC was safe, did not increase complication rates, shortened the time of hospitalization, and was associated with a marked improvement in the quality of life for the elderly. Surgeons were recommended to complete an operation in the laparoscopic setting as much as possible in patients with advanced age (12,(21)(22)(23)(24)(25). In our study, the mean age did not significantly differ between the two groups.…”
mentioning
confidence: 48%
“…During this study we had encountered multiple factors that resulted in conversion of laparoscopic cholecystectomy to open cholecystectomy with adhesion in calot's triangle dominated the intraoperative findings, followed by bleeding and acute inflammatory changes around gall bladder and intolerance to pneumoperitoneum [16,21,23].…”
Section: Discussionmentioning
confidence: 99%